MATIIGEN: Model-Driven Software Engineering Meets Precision Medicine for Improving Woman Healthcare - Pérez-Gómez, Ana; Costa, Mireia; S., Alberto García; Giachetti, Giovanni (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
Software engineering is a fundamental pillar for developing quality healthcare systems, with speciall atention in the Precision Medicine field, which tailors treatment based on individual genetic, environmental, and lifestyle variability. In this context, the MATIIGEN project aims to transition an intelligent software system for automated DNA variant interpretation from laboratory validation (TRL4) to operational clinical settings (TRL6). MATIIGEN is centered on Lipedema early detection, a chronic and widely under-researched disease primarily affecting women. Despite its high prevalence and significant physical and psychological impact, Lipedema was only recognized by the WHO in 2018, leaving its genetic basis largely unexplored. By applying a Model-Driven Software Engineering approach to the Lipedema use case, MATIIGEN will demonstrate how bridge the gap between management of complex clinical data and the descovery of actionable clinical insights, ultimately providing a systematic framework for developing high-quality systems in precision medicine.